The formation of direct collapse black holes under the influence of streaming velocities - Schauer, Anna T. P.; Regan, John; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2017)
We study the influence of a high baryonic streaming velocity on the formation of direct collapse black holes (DCBHs) with the help of cosmological simulations carried out using the moving mesh code arepo. We show that a streaming velocity that is as large as three times the root-mean-squared value is effective at suppressing the formation of H2-cooled minihaloes, while still allowing larger atomic cooling haloes (ACHs) to form. We find that enough H2 forms in the centre of these ACHs to effectively cool the gas, demonstrating that a high streaming velocity by itself cannot produce the conditions required for DCBH formation. However, we argue that high streaming velocity regions do provide an ideal environment for the formation of DCBHs in close pairs of ACHs (the “synchronised halo” model). Due to the absence of star formation in minihaloes, the gas remains chemically pristine until the ACHs form. If two such haloes form with only a small separation in time and space, then the one forming stars earlier can provide enough ultraviolet radiation to suppress H2 cooling in the other, allowing it to collapse to form a DCBH. Baryonic streaming may therefore play a crucial role in the formation of the seeds of the highest redshift quasars.
Gesehen am 14.12.2018